Prosedur Pemeriksaan CT-Scan Urografi Kontras Pada Kasus Kista Ginjal Di RSUP Persahabatan - Amraini Amraini; Annila Suryo Saputro (Journal of Educational Innovation and Public Health, 2024)
The urographic ct scan is a diagnostic procedure which aims comprehensively evaluate kidney, ureter, and bladder, as well as the general function of the urinary tracts. One of common pathologies detected on urographic examination is kidney cyst. The kidney cyst is a spherical or oval-shaped sac which contains a fluid form inside the kidney. This case study aims to explain the Urographic CT scan procedures with contrast media. This study assess the strengths and weakness of CT Urographic examinations with patients with kidney cysts. The study shows that CT Urographic exmination procedure involves informed consent, patient and equipment preparation, patient positioning, image acquisition and reconstruction. The study also shows that there was a difference in scanning phase on theory and clinical practices. While the theory states that the the Urographic CT examinations must be conducted with with four phases including non-contractional phases, cortikomedular phases, nefrographic and excretion phases, in clinical practices, the scanning was acquired with non-contrast phase, kidney phase, ureter phase and bladder phase.